Triflic Acid as Efficient Catalyst for the Hydroamination of Ethyl Acrylate with 2-Aminopyridines - Qian Xu, Wen; Jie Ren, Yu; Wei Wang, Qing; Xin Sun, Ying (Letters in Organic Chemistry, 2015)
Triflic acid (5mol%) is an efficient catalyst, which firstly applied to the anti-Markovnikov intermolecular hydroamination of ethyl acrylate with 2-aminopyridines, sharply improves yields as high as 96%, reduces reaction times as short as 12h. Moreover, the post-reaction process involves simple recrystallization in petroleum ether to obtain products in purity as high as 99%. The reaction mechanism is verified by crossover experiments, based on the catalytic mechanism of triflic acid previously proposed. The triflic acid is used for the reaction of a series of 2-aminopyridines with ethyl acrylate, and all the derivatives of ethyl 3-[(pyridine-2-yl)amino]propionate are characterized by 1H/13C NMR and HR-MS. The effect of electron-withdrawing/-donating substituent on the reaction is established by the reaction of substituted aminopyridines with ethyl acrylate. The reactivity of 5-methyl-2-aminopyridine is higher than those of other positional isomers of the same substituent. The reactivity of 2-aminopyridine with an electron-donating group is higher than that with an electron-withdrawing group at the same position. 2-Aminopyridines with weak electron-withdrawing substituent reacted more efficiently that those with strong electron-withdrawing substituents.
Keywords: catalytic mechanism